Efficacy and Safety of Budesonide in the Treatment of Eosinophilic Esophagitis: Updated Systematic Review and Meta-Analysis of Randomized and Non-Randomized Studies - Prashanth Rawla; Tagore Sunkara; Krishna Chaitanya Thandra; Vinaya Gaduputi (Adis, Springer Healthcare, 2018)
Abstract Background and Objective Eosinophilic esophagitis (EE) is an immune/antigen-driven inflammation that causes esophageal dysfunction. Budesonide has shown promising effect in the management of EE in multiple studies, and we therefore conducted this systematic review/meta-analysis to assess budesonide efficacy and safety in order to provide more updated and robust evidence. Methods In April 2018, we conducted a systematic electronic search through four databases: PubMed, Scopus, Web of Science (ISI), and Cochrane Central. All original studies reporting the efficacy of budesonide in the treatment of EE were included in our meta-analysis. The Cochrane Collaboration tool was employed to assess the risk of bias among included randomized controlled trials, while the Newcastle-Ottawa Scale was used for non-randomized studies. Results A total of 12 studies including 555 participants were included in our review. Budesonide showed marked efficacy at the level of histological response compared to placebo [risk ratio (RR) (95% confidence interval (CI)) 11.93 (4.82-29.50); p > 0.001]. Analysis of randomized and non-randomized studies revealed considerable reduction in eosinophil count, with a mean difference (MD) (95% CI) of − 69.41 (− 105.31 to − 33.51; p < 0.001) and 46.85 (33.93-59.77; p < 0.001), respectively. Similarly, there was a marked improvement in the clinical symptoms via the analysis of randomized and non-randomized studies, with an RR (95% CI) of 1.72 (1.22-2.41; p = 0.002) and MD (95% CI) of 2.45 (0.76-4.15; p = 0.005), respectively. Conclusion Budesonide showed significant effect at all treatment endpoints. However, since budesonide carries a risk of candidiasis and our inferences are based only on a small number of included studies, more research is warranted to clarify these results.